Implementasi Metode Regresi dengan Analisis Komponen Utama pada Kasus Diare Balita di Jawa Tengah (Jurnal EurekaMatika, 2025)
Multicollinearity is a condition that occurs in a regression model when there is a high correlation between independent variables. To address the problem of multicollinearity, the principal component regression technique is used. Through this approach, the causes of health problems can be identified more accurately. Central Java Province ranks 11th out of 34 provinces with a proportion of diarrhea cases in toddlers of 11.1%. The relatively high proportion of diarrhea in toddlers emphasizes the urgency of modeling its risk factors. Therefore, the purpose of this study was to apply the principal component regression method to cases of diarrhea in toddlers in Central Java. The regression model produced an R^2 value of 96.2%, which is interpreted as a very good model in identifying the relationship between the causes of diarrhea in toddlers and the number of toddlers suffering from diarrhea in districts/cities in Central Java. The factors that have a significant influence include the use of proper sanitation, malnourished toddlers, active integrated health posts, and fully immunized toddlers.Keywords: Analysis, Diarrhea, Multicollinearity, Principal component analysis, Regression, Toddlers.Multikolinearitas merupakan kondisi yang terjadi pada model regresi ketika adanya korelasi tinggi antara variabel independen. Untuk mengatasi masalah multikolinearitas maka digunakan teknik regresi komponen utama. Melalui pendekatan tersebut, faktor-faktor risiko kesehatan dapat diidentifikasi secara lebih akurat. Provinsi Jawa Tengah menduduki urutan ke 11 dari 34 provinsi dengan proporsi kasus diare pada balita ialah 11,1%. Angka proporsi diare balita yang cukup tinggi mempertegas urgensi pemodelan faktor risikonya, sehingga tujuan penelitian ini adalah menerapkan metode regresi komponen utama pada kasus diare balita di Jawa Tengah. Model regresi menghasilkan nilai  yang dapat diartikan sebagai model sangat baik dalam menggambarkan hubungan penyebab diare pada balita terhadap jumlah balita menderita diare di kabupaten/ kota di Jawa Tengah. Adapun faktor-faktor yang berpengaruh signifikan diantaranya pengguna sanitasi layak, balita yang kekurangan gizi, posyandu aktif, dan balita yang diimunisasi dasar lengkap.
Keywords: Analisis komponen utama; Balita; Diare; Multikolinearitas; Regresi